ISLAND MODE DETECTION METHOD BASED ON VOLTAGE AND FREQUENCY VARIANCE - MOHD KASSIM, FAIZ IZZUDDIN (IRC, 2019)
The concept of Distribution Generations (DG) technologies has introduced a power generation that are closer to the consumers. DG originally act as auxiliary power supply to microgrid which is a localized group of electricity sources and loads that typically operates connected to and synchronous with the traditional centralized utility grid. Concern arise when microgrid are disconnected from the utility grid which can cause unwanted condition where the voltage fundamental harmonics amplitude and frequency are out of control. Island mode detection methods functions to detect the event of island mode in order to disconnect the power supply to the local load to prevent damage to the microgrid’s equipment and machineries. This paper provide a review on the few active and passive island mode detection method that are used on the conventional power grid system. The performance of Sandia Frequency Shift (SFS) active island mode detection method are simulated on a Photovoltaic (PV) grid- connected microgrid circuit which are design and constructed using MATLAB/SIMULINK. Finally, this paper perform analysis on the effect of different type of local load to the overall performance of island mode detection method in disconnecting the power supply to the local load.